Numerical solution of a 2D lubrication model with Sommerfeld boundary conditions for hip prostheses - Weiss, Brenda Anahí (2015)
Prosthetic in-contact surfaces wear is one of the main causes of hip replacements fallure. Lubrication is essen- tial to reduce the friction and consequently the wear. A two- dimensional model based on a modified Reynolds equation, was used to aoalyze the lubricated contact In a hypothetical hip prosthesis. It is assumed that prosthesis is made of a me- tallic component and a low rigidity elastic porous material that can absorb or exude Duid. The Duid pressure and channel Dow shape were simultaneously solved by a double precision computer code based on the rmite element method, Newton?s method and parametric continuation. The Information provided by this model is extremely difficult to obtain by experimental methods. Results show that a great- er deformation capacity of the elastic material promotes a thicker lubrication mm and induces a better load distribution reducing normal stresses; whlle exudation capacity reduces friction and wear. The sub-ambient pressures predicted and the oscillatory solution, show the need of more realistic boundary conditions and fmite element mesh refinement.